Implementasi Diamond Strategy Framework pada Bimbingan Belajar Primagama - R.Hario Sulistianto, S.Sos., MBA (Management and Leadership Study Programme, 2018)
Strategy is a fundamental part of a business due to its purpose as a foundation forbusiness organization lay out their plan and action into commotion. One of the frameworks tosetup a strategy is diamond strategy. The strategy diamond framework can be used todevelop strategies in multi-business enterprises at all organizational levels and across marketor product. This article demonstrates how the framework yields insight that managers andexecutives need in order to make critical strategic decision. The power of single integratedapproach lies in its transformative ability to unite a form with one template based on acommon language and shared lexicon. This is a case study of Bimbingan Belajar Primagama,focusing on how the management examines the components of diamond strategy frameworkand it’s implementation in their organization. Primagama, one of the tuition center, gained alot of experience and successfully expanded its business to various parts of Indonesia.However, eventually, the rigors of competition forced some or even many tuition center toaccept a reduction in income and number of students. Several things affected the decline, suchas management, competitors, and marketing. Therefore, a prepared strategy or grandstrategy aimed at restoring its tutoring business on track and to reap maximum benefits.